CHARACTERIZATION OF 18S RIBOSOMAL RNA FRAGMENT FROM Solanum tuberosum L. var. Granola POTATO - Yunior William Susanto; Hermin Pancasakti Kusumaningrum; Siti Nur Jannah; Sri Rustini (Scripta Biologica, 2018)
Potato (Solanum tuberosum L.) is a prime horticultural commodity. One of the varieties of potato that widely cultivated in Indonesia is Granola. This study characterized the variety Granola based on the 18S sequences of rRNA gene fragment. The 18S sequences were used to distinguish the Granola and determine the differentiating characters from other Solanum based on those sequences data. The characterization was completed in three main steps including DNA isolation from potato leaf using Doyle & Doyle method, amplification of the 18S gene fragment, and DNA sequencing. The amplification of 18S gene fragment by a PCR method obtained 528 bp sequences. The BLAST search using NCBI web service confirmed that Granola potato has 99% matching sequence with S. tuberosum. The phylogenetic reconstruction further indicates the S. tuberosum var. Granola used in this study deeply nested with the reference sequence X67238.1, a potato from Europe.